Assessment of Density of Neovascularization in Lower Lip Squamous Cell Carcinoma in Relation to Neoplasm Differentiation Grade in Patients with and without Neck Lymph Nodes Metastasis - Kakasheva-Mazhenkovska, Lena; Kostovski, Marko; Gjokikj, Gjorgje; Janevska, Vesna (ID Design Press, 2019)
BACKGROUND: Squamous cell carcinoma (SCC) of the lower lip is a relatively rare carcinoma, with the incidence of 1 to 2%, but it is the most common carcinoma in the oral cavity accounting for 25-30% of all malignant oral tumours. AIM: This study aimed to determine the role of neovascularisation in the process of tumour progression. METHODS: We analysed the surgical specimens obtained from 60 patients with squamous cell carcinoma (SCC) of the lower lip. The examined group consisted of 45 specimens of patients without metastasis and 15 specimens of patients with metastasis in the regional lymph nodes. Histopathological slides were immunohistochemically stained with an antibody against CD34 and by hematoxylin & eosin staining for routine histopathological examination. RESULTS: The results obtained showed a statistically significant difference in the density of neovascularisation between groups of the SCC with different grade of differentiation (Kruskal-Wallis test: H (2, N = 60) = 30.0943, p = 0.00001). Statistical analysis also showed a significant difference in the density of vascularisation of lower lip SCC between patients without metastasis and patients with neck metastasis (Mann-Whitney U test, p = 0.000198). Applying Pearson’s chi-square test, we found a highly significant statistical difference in grade of SCC differentiation in patients with and without neck metastasis (p = 0.0000). CONCLUSION: In conclusion, the density of neoangiogenesis is increased in tumours with poorer differentiation and in patients with neck metastasis. So, the density of neovascularisation of the primary lip SCC may predict the tumour progression.
Keywords: squamous cell carcinoma; lower lip; neoangiogenesis; grade of differentiation; neck metastasis